Citizen participation from university classrooms: case of a legislative simulator - Legorreta Rebollo, Berenice (Ius Comitiãlis, 2023)
Significant knowledge from university classrooms can be considered a challenge for teachers, the objective of this paper is to demonstrate that the teacher-student task can have greater scope and visibility through simulation in real scenarios where ideas, knowledge, skills, and attitudes are put to the test, which generate citizen participation. Participatory democracy and the bibliographic and descriptive method are used as a theoretical framework, the participation of university students at the undergraduate level in a legislative simulator is presented, with a legislative proposal on the inclusion of the Mexican Sign Language (LSM) at the high school level education for the deaf community of the State of Mexico.